‘Cuida Nuestra Tierra’: Understanding Locally Specific Forms of Environmentalism in Lima, Peru - Wilkinson, Alisha Megan (Université d'Ottawa / University of Ottawa, 2020)
Growing concern about the ongoing environmental crisis has prompted an increased awareness of pollution and climate change. These grave environmental problems are often framed as pressing global issues, but they take unique forms in different locations. This thesis endeavours to contextualize these global issues and explore how they are apprehended at a local level. Through a focus on embodied experiential knowledge and social, political, and historical context, I have examined the specificity and local character of what it means to live with pollution and climate change in Lima, Peru. Based on ethnographic fieldwork in Lima’s Cono Sur, including participant observation and interviews, I argue that environmental understandings and practices must be seen as embodied, historical, and situated in time and space.
Keywords: Pollution; Climate Change; Environment; Lima; Peru; Anthropology